#54: Tuberculosis in South African Children with Cancer. (26th March 2021) - Naidu, G; Izu, A; Madimabe, R; Wainwright, R; Poyiadjis, S; MacKinnon, D; Rowe, B; Madhi, S A
Abstract: Background: Children with cancer are immunocompromised, with increased susceptibility to infections including infections with Mycobacterium tuberculosis . Method: This prospective study, enrolled children one-19 years old hospitalized for cancer treatment. Screening for M. tuberculosis infection was undertaken by tuberculin skin testing (Mantoux method), and ELISPOT (T-SPOT®.TB) (T-spot) on whole blood. Sputum/gastric-washings were investigated for microscopy and culture; and the diagnosis of probable TB was based on existing guidelines. We evaluated the burden of TB in South African children in a setting of high TB-HIV prevalence. Results: We enrolled 169 children, 82 (42.5%) with hematological malignancy (HM) and 87 (51.5%) with solid tumors (ST), median age 68.5 months, 10.7% HIV-infected. The majority had severe malnutrition, 78.3% using mid-upper arm circumference and 57.8% using arm muscle anthropometry. Five (2.9%) children with a reactive TST at enrollment, were empirically treated for TB, and were excluded from further analyses. The T-Spot yielded indeterminate/negative results in the first 100 children (including 2.9% who had a reactive TST), and further IGRA testing was terminated. Thirty-four (20.7%) children were diagnosed with TB, (70.6% with HM and 29.4% with ST). At the screening, 14 had indeterminate and 7 negative T-Spot results. Twelve (35.3%) of the 34 TB cases were culture-confirmed. The mean time from initiation of cancer treatment to TB diagnosis was 5.5 months and the time to TB diagnosis from presentation of malignant disease was 6.6 and 4.9 months for culture-confirmed and probable TB, respectively. The spectrum of cancer was acute lymphoblastic leukemia (ALL) ( n = 12/32, 37.5%), followed by non-Hodgkin Lymphoma ( n = 8/19, 42.1%; seven with HIV infection). The overall incidence (per 100 child-years) of TB was 7.6 (95% CI: 5.3–10.7), 11.3 (95% CI: 7.2–16.8) with HM and 4.3 (95% CI: 2.1–7.9) with ST. HIV-infected children had a higher rate of TB (19.3; 95% CI: 8.3–38) than those not (6.4; 95% CI: 4.2–9.4). Cancer type, HIV-status nor nutritional status was independently associated with risk of TB. Children who developed TB had a higher exposure period to high-dose corticosteroid courses (350 per 100 child-years) than those who did not (29.4 per 100 child-years; P < 0.001). Children with TB compared with those who remained TB-free were more likely to have been treated for septic episodes (SE) associated with profound neutropenia (322.2 vs. 31.3; P < 0.001), profound lymphopenia (288.9 vs. 27.2; P < 0.001) and profound monocytopenia (416.7 vs. 43.0; P < 0.001) prior to the diagnosis of TB. There were 26 deaths (76.5%) in the 34 children with TB and 39/83 (50.0%; P = 0.004) in those who did not develop TB. Eleven had ALL, eight NHL (seven living with HIV), 3 had acute myeloid leukemia, and one each had HIV-related Kaposi Sarcoma, Nephroblastoma, osteosarcoma, and adrenocortical-carcinoma. At the time of death, multiple pathogens were isolated (multi-drug-resistant bacteria, fungi, and respiratory viruses). Conclusion: Screening of children undergoing cancer treatment for MTB infection in a setting of high HIV and TB prevalence, was of limited value. The high rate of TB, and poor outcomes, emphasize the need for a high index of suspicion to diagnose TB and consideration for routine prophylaxis.